Ultrasound-guided microwave ablation: a promising tool in management of benign breast tumours. (3rd April 2017) - Zhou, Wenbin; Wang, Ruoxi; Liu, Xiaoan; Ling, Lijun; Liang, Mengdi; Li, Cuiying; Ma, Ge; Li, Li; Pan, Hong; Gong, Haiyan; Ding, Qiang; Wang, Shui
Abstract: Purpose: Non-surgical treatments for benign breast tumours have clinical goals of stopping growth and/or reducing (removing) palpable tumours effect without leaving a surgical scar. The purpose of this non-randomised prospective clinical trial was to assess imaging and clinical outcomes of microwave ablation (MWA) in the treatment of benign breast tumours regardless of the distance from the tumour to the skin and chest wall. Methods: With approval of the institutional ethics committee and written informed consent, 39 patients with 44 core-biopsy-proved benign breast tumours 3.0 cm or less in diameter assessed by using ultrasound (US) and contrast-enhanced ultrasound (CEUS) were prospectively recruited. US-guided MWA was performed under local anaesthesia. The patients were followed up with physical examination, ultrasound elastography and CEUS. Results: The MWA procedure with a mean duration of 74.3 s ± 26.5 was well accepted and tolerated in 41 cases except for three cases. Of 41 tumours with follow-up data, 40 (97.5%; 95% confidence interval: 87.1%, 99.9%) showed complete ablation assessed by using CEUS. The mean volume of the ablated tumours decreased significantly ( p  = .005) during follow-up. The strain ratio 1-3 months after ablation was higher than that before ablation, and became low 6 months after ablation ( p  = .022). No epidermal burn was observed in all cases with a mean distance of 7.5 mm ±3.3 from the tumour to the skin. Conclusions: MWA is a safe and effective minimally invasive "patient-friendly" procedure with a very short duration for the treatment of benign breast tumours.